2014
DOI: 10.1111/ipd.12092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of traumatic dental injuries and malocclusions on quality of life of preschool children: a population‐based study

Abstract: The presence of complicated TDI and dental caries were associated with worse OHRQoL of Brazilian preschool children, whereas malocclusions do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
108
3
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(135 citation statements)
references
References 21 publications
9
108
3
15
Order By: Relevance
“…1,2,10,22 Indeed, both the mean SOHO-5 total and item scores were greater among children with dental caries, in agreement with previous study data. 7,10,11 It was noted that, in addition to cavitated lesions, white spots were associated with OHRQoL for some items and in the multivariate model for the child version. The reason could be that these spots cause aesthetic discomfort, which may impact social interaction and the child's self-image.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,10,22 Indeed, both the mean SOHO-5 total and item scores were greater among children with dental caries, in agreement with previous study data. 7,10,11 It was noted that, in addition to cavitated lesions, white spots were associated with OHRQoL for some items and in the multivariate model for the child version. The reason could be that these spots cause aesthetic discomfort, which may impact social interaction and the child's self-image.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 Studies involving the SOHO-5 that evaluate the perception of parents/guardians and children have demonstrated that five-year-old children are capable of providing their own perceptions regarding their OHRQoL. 4,7,9,10,11 However, their comprehension is dependent on social, emotional, cognitive and linguistic development. 12 Moreover, children in this age group are influenced by their parents/guardians, who are the main decision makers regarding healthcare issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bear in mind that other studies have reported lower rates than this study. 2,3,4,5 A longitudinal study found that children with anterior open bite, increased overjet and posterior crossbite in the primary dentition are at greater risk of exhibiting the same characteristics in the mixed dentition. 6 A clinical trial reported that the diagnosis of malocclusion in the mixed and permanent dentitions may be based on bite characteristics in the primary dentition.…”
Section: Introductionmentioning
confidence: 99%
“…12 The majority of studies employing the ECOHIS have not found a significant association between malocclusion and impact on quality of life among preschool children. 2,3,5,13,14,15 However, many studies have considered only the presence/absence of malocclusion in the analysis. Thus, the aim of the present study was to evaluate associations between different types of malocclusion and the impact on the quality of life of preschool children and their families.…”
Section: Introductionmentioning
confidence: 99%